Aegle marmelos Mediated Green Synthesis of Different Nanostructured Metal Hexacyanoferrates: Activity against Photodegradation of Harmful Organic Dyes. (29th February 2016) - Jassal, Vidhisha; Shanker, Uma; Kaith, B. S.
Abstract : Prussian blue analogue potassium metal hexacyanoferrate (KMHCF) nanoparticles Fe4 [Fe(CN)6 ]3 (FeHCF), K2 Cu3 [Fe(CN)6 ]2 (KCuHCF), K2 Ni[Fe(CN)6 ]·3H2 O (KNiHCF), and K2 Co[Fe(CN)6 ] (KCoHCF) have been synthesized using plant based biosurfactant Aegle marmelos (Bael) and water as a green solvent. It must be emphasized here that no harmful reagent or solvent was used throughout the study. Plant extracts are easily biodegradable and therefore do not cause any harm to the environment. Hence, the proposed method of synthesis of various KMHCF nanoparticles followed a green path. The synthesized nanoparticles were characterized by powder X-ray diffraction (PXRD), Field-Emission Scanning Electron Microscopy (FE-SEM), Transmission Electron Microscopy (TEM), and Fourier Transform Infrared Spectroscopy (FT-IR). MHCF nanoparticles were used for the photocatalytic degradation of toxic dyes like Malachite Green (MG), Eriochrome Black T (EBT), Methyl Orange (MO), and Methylene Blue (MB). Under optimized reaction conditions, maximum photocatalytic degradation was achieved in case of KCuHCF nanoparticles mediated degradation process (MG: 96.06%, EBT: 83.03%, MB: 94.72%, and MO: 63.71%) followed by KNiHCF (MG: 95%, EBT: 80.32%, MB: 91.35%, and MO: 59.42%), KCoHCF (MG: 91.45%, EBT: 78.84%, MB: 89.28%, and MO: 58.20%).